KONTRIBUSI DUKUNGAN ORANGTUA TERHADAP TINGKAT ASPIRASI PENDIDIKAN LANJUTAN - Triyono, Tri (Jurnal Pelangi : Research of Education and Development, 2016)
This research was conducted from the students low aspiration level toward higher education. The higher education aspiration level were affected by parents support. This research was aimed to describe: (1) the parents support and the higher education aspiration level, (2) the contribution of the parents support toward higher education aspiration level. This correlational descriptive researchapplied quantitative method. The population of this research were 245 students of SMA Negeri 3 Mukomuko on grade XI and XII, also 141 students there were chosen by proportional stratified random sampling technique. The instrument of the research was a questionnaire. The validity of parents support instrument was 0.768 and the higher education aspiration level was 0.652. The reliability of parents support instrument was 0.966 and the higher education aspiration level was 0.655. The data obtained were analyzed by using descriptive statistic and simple regression. The research findings indicated that: (1) in average, the parents support was in high category, the students’ and the higher education aspiration level was in very high category, (2) the parents support contributed 14.4% (R=0.379, on significance level 0.000) toward higher education aspiration level.Keywords : Parents Support,  Aspiration Level